Herbicide symptomology and the mechanism of action of methiozolin. Issue 1 (3rd January 2021) - Brabham, Chad; Johnen, Philipp; Hendriks, Janneke; Betz, Michael; Zimmermann, Alexandra; Gollihue, Jarrad; Serson, William; Kempinski, Chase; Barrett, Michael
Abstract: Methiozolin is a new herbicide with an unknown mechanism of action (MOA) for control of annual bluegrass ( Poa annua L.) in several warm- and cool-season turfgrasses. In the literature, methiozolin was proposed to be a pigment inhibitor via inhibition of tyrosine aminotransferases (TATs) or a cellulose biosynthesis inhibitor (CBI). Here, exploratory research was conducted to characterize the herbicide symptomology and MOA of methiozolin. Arabidopsis ( Arabidopsis thaliana L.) and P. annua exhibited a similar level of susceptibility to methiozolin, and arrest of meristematic growth was the most characteristic symptomology. For example, methiozolin inhibited A. thaliana root growth (GR50 8 nM) and shoot emergence (GR80 ˜50 nM), and apical meristem growth was completely arrested at rates greater than 500 nM. We concluded that methiozolin was neither a TAT nor a CBI inhibitor. Methiozolin had a minor effect on chlorophyll and alpha-tocopherol content in treated seedlings (<500 nM), and supplements in the proposed TAT pathway could not lessen phytotoxicity. Examination of microscopic images of roots revealed that methiozolin-treated (100 nM) and untreated seedlings had similar root cell lengths. Thus, methiozolin inhibits cell proliferation and not elongation from meristematic tissue. Subsequently, we suspected methiozolin was an inhibitor of the mevalonic acid (MVA) pathway, because its herbicidal symptomologies were nearly indistinguishable from those caused by lovastatin. However, methiozolin did not inhibit phytosterol production, and MVA pathway metabolites did not rescue treated seedlings. Further experiments showed that methiozolin produced a physiological profile very similar to cinmethylin across a number of assays, a known inhibitor of fatty-acid synthesis through inhibition of thioesterases (FATs). Experiments with lesser duckweed ( Lemna aequinoctialis Welw.; syn. Lemna paucicostata Hegelm.) showed that methiozolin also reduced fatty-acid content in Lemna with a profile similar, but not identical, to cinmethylin. However, there was no difference in fatty-acid content between treated (1 µM) and untreated A. thaliana seedlings. Methiozolin also bound to both A, thaliana and L. aequinoctialis FATs in vitro. Modeling suggested that methiozolin and cinmethylin have comparable and overlapping FAT binding sites. While there was a discrepancy in the effect of methiozolin on fatty-acid content between L. aequinoctialis and A. thaliana, the overall evidence indicates that methiozolin is a FAT inhibitor and acts in a similar manner as cinmethylin.